Investigação celular e molecular sobre as condições de agravo na fertilidade do homem - Belardin, Larissa Berloffa [UNIFESP] (2019)
Objective: To evaluate whether the extracellular environment and its interaction with sperm are related to the two main described causes of alteration in male fertile potential, namely varicocele and sperm DNA fragmentation. Methods: This thesis was divided into 2 chapters, where the first one aims to identify molecular changes in the extracellular environment of men with varicocele. This chapter has been divided into 2 articles. In article I it was verified: (i) the effect of varicocele; and (ii) effect of varicocelectomy on the levels of cysteine rich secretory protein 3 (CRISP-3) in seminal plasma by western blotting. In article II, the expression of microRNAs present in seminal plasma extracellular vesicles in men with varicocele, and before and after varicocelectomy was evaluated using microarray. The second chapter sought to better understand whether the extracellular environment and its interaction with sperm reflect the sperm DNA fragmentation status. The first article evaluated, using a Multiplex assay, the expression of proteins from the Matrix metalloproteinases (MMPs) family and their inhibitors named Tissue inhibitors of metalloproteinases (TIMPs) in seminal plasma of men with high and low sperm DNA fragmentation. The second article verified the presence of Epididymal sperm-binding protein 1 (ELSPBP1) in seminal plasma samples and sperm with high and low DNA fragmentation by western blotting and identified its location in the sperm by immunocytochemistry and verified if this protein is capable of separating sperm with high levels of DNA fragmentation from the healthy population, using immunomagnetic cell separation. Results: Regarding the study of varicocele (chapter I), in article I it was found that men with varicocele have higher CRISP-3 seminal levels when compared to controls. CRISP-3 levels decreased after varicocelectomy. In Article II, it was observed that there are microRNAs present in seminal plasma extracellular vesicles that reflect the pathogenic process of varicocele before varicocelectomy. While other microRNAs are involved in fertility protective processes. In Chapter II, which studied the pathology of sperm DNA fragmentation, in article I, lower levels of seminal plasma MMP-2, MMP-7, TIMP-1, TIMP-2 and TIMP-4 were observed in high when compared to the low sperm DNA fragmentation group. In logistic regression analysis, proteins MMP-2, MMP-7 and TIMP-4 classified the samples as low and high DNA fragmentation. With respect to article II, the protein ELSPBP1 is more expressed in sperm from samples with higher levels of sperm DNA fragmentation when compared to samples with lower levels of DNA fragmentation. This protein, in human sperm is preferentially located in the region of the head and was efficient to separate sperm with higher levels of DNA fragmentation from the health population. Conclusion: The extracellular environment and its interaction with sperm are related to varicocele and sperm DNA fragmentation.